Single nucleotide polymorphism in the seed region of microRNA alters the expression of its mature microRNA / Leong Pei Li - Leong, Pei Li (2013)
MicroRNAs (miRNA) are a class of non-coding RNAs with approximately 18 to 28 nt, which are important in post-transcriptional gene regulation. In this study, potential single nucleotide variant within seed region sequence of mature miRNAs of Homo sapiens was identified. Mature miRNA sequences of Homo sapiens were collected from miRBase database. A total of 1344 mature miRNA sequences were used to compare with single nucleotide variant sequence in UCSC database to search for candidate miRNA variant. Fourty-two mature miRNAs that have single nucleotide variant on seed-region were identified. Prediction of the secondary structure with MFOLD had identified a total of fourteen potential miRNAs that have a single nucleotide variant on the seed region. Two mature miRNAs with SNP on their seed-region had been chosen to validate experimentally with real-time PCR approach; miR124-3 (miRBase ID MI0000445) and miR-662 (miRBase ID MI0003670). These two potential single nucleotide variant on the seed region sequence of mature miRNAs were found to enhance the expression of its mature miRNA. The nucleotide change on the seed region of miR124-3 and miR-662 is suspected to provide stable secondary structure of pri-miRNA and pre-miRNA compare to the wild-type allele of miRNAs. The increased expression of specific miRNAs could possibly render the miRNA to act as an oncomiR or vice versa as a tumour suppressor miRNA, hence this study emphasizes that a single nucleotide change on the seed-region of mature miRNA could potentially lead to widespread phenotypic effects and broadens our understanding on miRNA biogenesis.